Base genética de los cultivares de arroz de riego liberados en Venezuela - Acevedo, M.A.; Torres Castro, Edgar Alonso; Moreno, O; Álvarez, R.; Torres, O.; Castrillo, W.; Torrealba N., G.T.; Reyes, E; Salazar, M.; Navas, M (2007)
The genealogy of 19 varieties of irrigated rice, Oryza sativa L., liberated in Venezuela during the years 19782006, were analyzed with the objective to determine the number of ancestors present, also to estimate its relative genetic contribution. The results indicated that the majority (56%) of the ancestors were originated in Asia, while the ones of American and African origin provided 10% each one. The pedigree analysis showed that 59 ancestors contributed with 99,99% of the genetic base and only 5 ancestors are present in all the varieties studied, with a genetic accumulated contribution (CGA) of 51,89%. When the genetic base of rice in Venezuela is analyzed, only 16 ancestors lines possesses a CGA of 80,47%. If the material that contributed with more than 2% of the genes are considered, this number is reduced to 12 ancestors and its CGA is of 74,48%. The results allow to infer that the genetic base of rice in Venezuela is more stretch than that of Latin America and similar to that of irrigate rice in Brazil. It is recommended to increase the genetic base of the Venezuelan varieties, which will allow, in the short and middle time, to win in selection, in addition to avoid possible genetic vulnerability. This information is of great importance because it allows to address future crossing in the breeding program of rice in Venezuela.